Congenital midureteral stenosis in children: a 13-year retrospective study based on data from a large pediatric medical center - Zhaoyi Meng (BMC, 2021)
Abstract Background Midureteral stenosis is very rare in children and can cause congenital hydronephrosis. We report our experience treating children with congenital midureteral stenosis at our center, focusing on the differences in preoperative diagnosis and treatment compared with other congenital obstructive uropathies. Methods We retrospectively reviewed the medical records of 26 children diagnosed with congenital midureteral stenosis at our center between January 2007 and December 2020, such as preoperative examination methods, intraoperative conditions, and postoperative follow-up results. Results Of the 1625 children treated surgically for ureteral narrowing, only 26 (1.6%) were diagnosed with midureteral stenosis, including 15 infants and 11 children. Eighteen (69.2%) were boys, 13 (50%) were affected on the left side, and 23 (88.5%) had isolated ureteral stenosis. Overall, 13 (50%) of the children presented with prenatal hydronephrosis, and 13 (50%) presented with abdominal pain or a mass. All the children had undergone urinary ultrasound and intravenous urography preoperatively; the diagnostic rate of ultrasound was 92.3%. Only 7 (26.9%) children had undergone pyelography. All the children had undergone surgery. The ureteral stenotic segment was less than 1 cm long in 25 (96.2)% of the children. The mean follow-up duration was 22 months (range: 6–50 months). One child developed anastomotic strictures. Urinary tract obstruction was relieved in the other children without long-term complications. Conclusions Congenital midureteral stenosis is rare, accounting for 1.6% of all ureteral obstructions, and its diagnosis is crucial. Urinary ultrasound has a high diagnostic rate and should be the first choice for midureteral stenosis. Retrograde pyelography can be used when the diagnosis is difficult, but routine retrograde pyelography is not recommended. Congenital ureteral stenosis has a relatively short lesion range, largely within 1 cm. The treatment is mainly resection of the stenotic segment and end-to-end ureteral anastomosis, with a good prognosis.